Pengujian Validitas dan Reliabilitas Model UTAUT 2 dan EUCS Pada Sistem Informasi Akademik - Shinta Aprilisa; Samsuryadi Samsuryadi; Sukemi Sukemi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The research instrument is used to collect data or measure the object of a study. The purpose of this study was to determine which instruments were declared valid and reliable and to find out the variables with the highest validity and reliability values. Validity testing is carried out to determine the effectiveness of an instrument, while reliability testing is carried out to show the level of reliability of the indicators used. Testing the validity and reliability using software SmartPLS version 3.3.2 with a measurement scale that is Likert scale. Validity testing is done by looking at the average variance extracted (AVE) value and the comparison of the latent variable correlations values, while reliability testing is done by looking at the composite reliability value. The population in this study were active students at the State Islamic University (UIN) Raden Fatah Palembang, totaling 19,260 students with the determination of the sample using the Slovin formula with a level of significance = 5%. Data collection in this study was carried out by distributing online questionnaires. The questionnaire was made based on indicators on the model used, where the models used were UTAUT 2 and EUCS. The UTAUT 2 model can be used to measure the level of user acceptance of the system consisting of the variables of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, perceived value, habit, and behavioral intention. Furthermore, the EUCS model is used to measure the level of user satisfaction which consists of content, accuracy, format, ease of use, timeliness, and user satisfaction variables. The results of the validity and reliability testing state that all indicators are valid and reliable with an AVE value > 0.50 in the validity test and the composite reliability value > 0.70 in the reliability test. The validity test with the highest value is found in the ease of use variable with an AVE value of 0.826 and reliability testing with the highest value is found in the performance expectancy variable with a composite reliability value of 0.924. With this research, it is expected to obtain variables in the model to evaluate user acceptance and satisfaction with academic information systems